2014
DOI: 10.3329/bmrcb.v39i3.20313
|View full text |Cite
|
Sign up to set email alerts
|

Microbial contamination in herbal medicines available in Bangladesh

Abstract: Plants have long been used as herbal medicines in many countries. However, microbial contamination of these medicines may affect human health. Present study was performed to assess the pathogenic proliferation in the locally available commercial herbal oral medicines. The pathogenic load was compared with the microbiological standard given by the British Pharmacopoeia. Out of 85 oral liquid samples, 2 were found to be highly contaminated with a total aerobic bacterial load of 1.24×10 5 cfu/ml, 10 samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Due to the increased rate of resistance and several adverse effects for toxicity of the synthetic drugs, natural products like herbs have attracted lots of interest to be a suitable drug alternatives or sources for new drug discoveries in recent years [8,[24][25][26][27][28][29][30][31][32][33][34][35][36][37]. G. lucidum has already proved its competency as medicinally active mushrooms with a wide range of therapeutic and biological effects [3-5, 7, 9, 23].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the increased rate of resistance and several adverse effects for toxicity of the synthetic drugs, natural products like herbs have attracted lots of interest to be a suitable drug alternatives or sources for new drug discoveries in recent years [8,[24][25][26][27][28][29][30][31][32][33][34][35][36][37]. G. lucidum has already proved its competency as medicinally active mushrooms with a wide range of therapeutic and biological effects [3-5, 7, 9, 23].…”
Section: Resultsmentioning
confidence: 99%
“…Natural products have long been used as precious sources for the formulation of useful drugs (Cragg and Newman 2013 ; World Health Organization 2013 ; Veeresham 2012 ; Gyasi et al 2011 ; Izzo and Ernst 2009 ; Kraft 2009 ). Besides combating diseases with the use of antibiotics, herbal medicines are also widely known for their implications in mitigating a number of clinical complications (Behera et al 2013 ; Noor et al 2013a ; Tabassum and Ahmad 2011 ; Damery et al 2011 ; Ernst 2011 ; Mendes et al 2010 ). According to WHO estimation, 21,000 plants have been found globally to be used for medicinal purposes (Umashanker and Shruti 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, a huge pharmacological evaluation and ethnomedicinal survey of medicinal plants have been conducted; however, the microbiological survey of herbal medicines have not been accomplished well (Das et al 2012 ; Rahmatullah et al 2010 ). While the research on microbiological assessment of the pharmaceutical products is abundant in this country, such work on the herbal products is quite petite (Das et al 2013 ; Khanom et al 2013 ; Noor et al 2013a ; Moniruzzaman et al 2012 ; Hossain 2009 ). Along these lines, present study endeavored to assess microbiological contamination level within the commonly available herbal medicines; and to further demonstrate the anti-bacterial activity of the tested medicinal samples.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have revealed that due to unscientific mode of harvesting, drying, transportation, cleaning and handling of these herbal preparations, the raw plants are prone to infestations and exposed them to different kinds of microbial contaminants (Stevic et al, 2012). The dominating contaminants are the bacterial endospores and fungal spores while the remaining are heavy metals and viruses originating from the soil (Adeleye et al, 2005;Kaume et al, 2012;Ting et al, 2013;Noor et al, 2014).…”
Section: Introductionmentioning
confidence: 99%